ESTÁGIO SUPERVISIONADO EM PSICOLOGIA E PROCESSOS CLÍNICOS I E II - Aires, Juliana F.; Bertasso, Bruna; Dalcin, Daniela; Morini, Fernanda; Castilho, Normandia C. G. (Salão do Conhecimento, 2013)
Resumo